Transfer Pricing and Its Relationship with Effective Tax Rate, Profitability, and Foreign Ownership - Indrawaty, Runy Rusdyantinah; Usman, Asri; Alimuddin, Alimuddin (Faculty of Economics and Business, Hasanuddin University, 2023)
This study aims to investigate the influence of effective tax rate and profitability on transfer pricing moderated by foreign ownership of consumer non-cyclical enterprises listed on the Indonesia Stock Exchange. Transfer pricing has become an intriguing subject due to firms' desire to reduce tax expenses to generate higher profits. The hypothesis was tested using Moderated Regression Analysis (MRA), which found that the effective tax rate has no significant effect on transfer pricing, however, profitability influences companies' decision to perform transfer pricing. It has been proved that foreign ownership has a moderating effect on the effective tax rate, profitability, and the transfer pricing interaction.